Direito administrativo do medo: o controle administrativo da gestão pública no Brasil - Sousa, Francisco Arlem de Queiroz (2021)
Fear is a feeling related to the idea of a threat, physical or moral, or danger, real or abstract, of being hit by some evil. He is one of the four giants of the soul, connected to human existence, changing according to times, places and people. Currently fear has its roots in Brazilian administrative law and today it participates in public management. It has become common for reports of managers terrified by the leviathan controller that intimidates many due to the wide powers they hold, exercised practically without checks and balances. With the promulgation of the 1988 Constitution and the re-democratization, the control mechanisms over the actions of the Public Administration were expanded. It so happens that the constitutional model, dubbed “multiple whips”, has provoked negative externalities, because the institutions instead of cooperating, compete for reputation as a strategy of power, they use legal principles indiscriminately as a camouflage for solipsistic decisions, in addition to seize a popular fascination for creating a world where anything is possible, especially when there is no responsibility to put one's own decisions into practice. The devastating effects of controlling activism are perceived, among other symptoms, in the countless stopped works, the result of the “blackout of pens”. Accountability overload has chased away skilled professionals from public administration staff and current occupants feel childish, when they are not treated as objects of law, just like the pen they fear to use when they have the discretion that is given them by law, but that has been captured by the controllers. In addition to traditional bibliographic and documentary research, sought, in the present work, sources capable of producing knowledge applied to practice were sought, aiming to change paradigms and mentalities, aiming at a future where administrative control is not a reason for panic, especially considering the features of administrative law modern, that walk through the dialogue between the institutions, through consensus, through a more realistic and less idealized vision of public management, working towards the realization of the fundamental right to good administration.